Determinants of Mobile Broadband Penetration: An Empirical International Study - Athanasios Pachis; Demetrius Yannelis (International Telecommunications Society (ITS), 2018)
This study examines relevant factors that determine mobile broadband penetration for a large set of international countries, using instrumental variables econometric techniques. Furthermore it tests for stationarity of the variables using appropriate tests when cross sectional dependence is present. In respect to our main findings we conclude that lower cost of mobile services internet content facilitates mobile broadband diffusion. Moreover we highlight the importance of developing e-services in promoting mobile broadband. In addition we find that mobile and fixed broadband are complements signifying that they are beneficial spillover effects in promoting either of them. Concerning socioeconomic factors we find that factors such as education, income, percentage of urban population and percentage of population between 15-64 years old incite mobile broadband proliferation. Finally countries with multiple mobile standards have significantly higher mobile broadband penetration.
Keywords: 330